Foreign Aid and the Quest for Poverty Reduction: Is Aid to Agriculture Effective? - Kaya, Ozgur (2013)
Development statistics estimate that three quarters of the poor live in rural areas and most of them depend on agriculture and related activities for their livelihood. Consequently, research focusing on economic growth and poverty reduction has found that sustainable rapid transition out of poverty requires a special emphasis on the agricultural sector. This study contributes to the debate on aid effectiveness by disaggregating total aid into subcategories and specifically investigating the relationship between aid given to the agricultural sector and poverty reduction. If agricultural development is more effective in reducing poverty than some other types of development, then foreign aid directed towards agriculture may be more efficient in increasing the well-being of the poor than aid directed to some other sectors or uses. Our analysis uses panel data for developing aid recipient countries to empirically test this relationship. We find a significant relationship between agricultural aid and poverty reduction in our estimates.